Biogenic Iron Dust: A Novel Approach to Ocean Iron Fertilization as a Means of Large Scale Removal of Carbon Dioxide From the Atmosphere - Emerson, David (Frontiers in Marine Science, 2019)
This is a proposal for ocean iron fertilization as a means to reduce atmospheric carbon dioxide levels. The idea is to take advantage of nanoparticulate, poorly crystalline Fe-oxides produced by chemosynthetic iron-oxidizing bacteria as an iron source to the ocean. Upon drying these oxides produce a fine powder that could be dispersed at altitude by aircraft to augment wind-driven Aeolian dust that is a primary iron source to the open ocean. Based on Fe-oxidation rates for natural populations of iron-oxidizing bacteria it is estimated 1,500 hectares of production ponds (1m x 100m x 100m) would be required to produce sufficient iron dust to supply the 30% of the global ocean that is iron-limited. In theory, iron replete conditions will stimulate the biological pump to quantitatively remove enough carbon dioxide from the atmosphere to partially mitigate anthropogenic inputs. Modifications to existing technologies would satisfy most of the technological challenges. Addition of biogenic iron to meso-scale eddies could provide an effective means of testing this process. Nonetheless, there are many unknowns, thus any such effort will require research and development integrated across oceanographic and Earth science disciplines to determine its long term efficacy.